So, what"s your story? – The role of storytelling in nurturing inclusive congregational identity - Naidoo, Marilyn ca. 20./21. Jh. (HTS teologiese studies, 2019)
South African churches are struggling to form cohesive communities and strategies are needed to bring people together. Because of a deficiency in trust, people are reluctant to get to know each other, impacting on the quality of relationships and a positive sense of belonging and community. Congregations need to find ways to nurture an inclusive identity instead of the current norm of all-white or all-black churches, which can be perceived as being inaccessible or exclusive. Innovative strategies like storytelling can unlock the power to understand each other breaking down prejudice, racism and xenophobia. Because intercultural socialisation is found wanting in congregations, sharing different perspectives and experiences can deepen engagements overcoming superficial interactions. This article expands on how storytelling can be used to facilitate an inclusive and intercultural congregational identity through identity formation, liberative practices of reconciliation, community building and as an educational resource.